Portable Document Format File Showing the Surface Models of Cadaver Whole Body - Shin, Dong Sun (The Korean Academy of Medical Sciences, 2012)
In the Visible Korean project, 642 three-dimensional (3D) surface models have been built from the sectioned images of a male cadaver. It was recently discovered that popular PDF file enables users to approach the numerous surface models conveniently on Adobe Reader. Purpose of this study was to present a PDF file including systematized surface models of human body as the beneficial contents. To achieve the purpose, fitting software packages were employed in accordance with the procedures. Two-dimensional (2D) surface models including the original sectioned images were embedded into the 3D surface models. The surface models were categorized into systems and then groups. The adjusted surface models were inserted to a PDF file, where relevant multimedia data were added. The finalized PDF file containing comprehensive data of a whole body could be explored in varying manners. The PDF file, downloadable freely from the homepage (http://anatomy.co.kr), is expected to be used as a satisfactory self-learning tool of anatomy. Raw data of the surface models can be extracted from the PDF file and employed for various simulations for clinical practice. The technique to organize the surface models will be applied to manufacture of other PDF files containing various multimedia contents.